Design and Development of Supporting Applications “E-MPKK” For Leraning Media of Midwife and Enterpreneurship Managament Clinic Practice - Yuseva Sariati; Ningrum Paramita Sari; Harun Al Rasyid; Suryo Ediyono (GLOBAL HEALTH SCIENCE GROUP, 2022)
Learning Center for Midwifery Service Management and Entrepreneurship to manage management reports, proposals, and role plays. The first purpose and benefit of this research is to design and build a prototype software application